Answer:
It is actually D) Age
Step-by-step explanation:
Because A) B) and C) can both be brought to court and the company or business will always lose, because those are all major discriminates that the court will favor the plaintiff but age is a total viable way to discriminate against a person.
And I took it on a test too.
By the Pythagoras theorem we know that the if the square of the longest side of the triangle is equal to the sum of the square of other two sides.
The triangle formed by the sides 3.8 cm ,3.7 cm, and 5 cm is acute angle triangle.
How to find the type of triangle?
By the Pythagoras theorem we know that the if the square of the longest side of the triangle is equal to the sum of the square of other two sides. Thus,
By this law it is observed that,
The sides of the given triangle are 3.8 cm ,3.7 cm, and 5 cm.
Here the longest side is 5 cm. Thus check the type of triangle using above formula. Longest side,
Other two sides,
Therefore,
Hence the triangle formed by the sides 3.8 cm ,3.7 cm, and 5 cm is acute angle triangle.
Learn more about the type of triangle here;
10,010 mm3
7,680 mm3
10,240 mm3
Answer:
The answer to your question is 10240 mm³
Step-by-step explanation:
Data
length of the base = 32 mm
length of the height = 34 mm
Formula
Volume of a pyramid = 1/3 x Area of the base x length of the height
Process
1.- Calculate the area of the base
Area = side x side
= 32 x 32
= 1024 mm²
2.- Find the height of the pyramid using the Pythagorean theorem
height² = 34² - 16²
height² = 1156 - 256
height² = 900
height = 30
3.- Calculate the volume of the pyramid
Volume = 1/3Area x height
= 1/3(1024 x 30)
= (30720)/3 mm³
= 10240 mm³
Answer:
The answer is 5,940mm^3
Step-by-step explanation:
I got is right on my test
-9x - 3y = -15
Answer: (1,2)
Step-by-step explanation:
You must:
- Multiply the first equation by 3.
- Add both equations.
- Solve for the variable left. In this case will be x.
Then:
Substitute x=1 into any of the original equtions and solve for y:
The solution is: (1,2)
Answer:
The solution of the system of equation is (1 , 2)
Step-by-step explanation:
The system of equation is:
* 13x + y = 15 ⇒ (1)
* -9x - 3y = -15 ⇒ (2)
- By using elimination ⇒ we must make on of the
two variables in the two equations has the same value
with different sign
- So we will multiply equation (1) by 3 to eliminate y
∴ 3(13x) + 3(y) = 3(15)
∴ 39x + 3y = 45 ⇒ (3)
- Now add (2) and (3)
∴ 39x + -9x = 45 + -15
∴ 30x = 30 ⇒ ÷ 30 both sides
∴ x = 1
- Substitute the value of x in equation (1) or (2)
- Lets use (1)
∴ 13(1) + y = 15
∴ 13 + y = 15 ⇒ subtract 13 from both sides
∴ y = 15 - 13
∴ y = 2
∴ The solution of the system of equation is (1 , 2)
A. Parasailing: $39; Horseback Riding: $48
B. Parasailing: $51; Horseback Riding: $30
C. Parasailing: $27; Horseback Riding: $46
D. Parasailing: $63; Horseback Riding: $24
Answer:
Horseback riding costs $30 and parasailing costs $51, so B.
Step-by-step explanation:
This is answered by using simultaneous equations, let x be parasailing and y be horseback riding.
3y + 2x = 192
2y + 3x = 213
Multiply each equation by the number in front of the y of the other equation:
2 x (3y + 2x = 192)
3 x (2y + 3x = 213)
Which results in:
6y + 4x = 384
6y + 9x = 639
Simply minus the two equations to get rid of the y:
6y - 6y = 0
4x - 9x = -5x
384 - 639 = -255
The negatives cancel out which give a result:
5x = 255
x =
x = 51
So parasailing costs $51
Now you can simply plug this value into one of the equations:
3y + (2 x 51) = 192
192 - 102 = 3y
90 = 3y
y =
y = 30
So horseback riding costs $30!
Hope this helps.